Digital Gamification in Rural Elementary Education: Enhancing Student Engagement and Learning Outcomes through Quizizz and Competition-Based Learning - Fahmi Fuadi; Fenny Alya Romadhona; Faiq Afifah; Moch. Farich Alfani (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
Digital learning in rural primary schools is often constrained by limited devices, unstable internet access, and uneven teacher readiness. This study examines Quizizz Paper Mode and a team-based competition model adapted from the “Clash of Champions” format as a game-based formative assessment strategy in a rural Indonesian primary school. Using a pre-experimental mixed-methods design, the study involved 30 fifth-grade students at SDN Sindangheula 01 and six teacher informants. Data were collected through a 20-item achievement test, classroom observation, student response indicators, interviews, and documentation. The findings show that students’ mean score increased from 62.3 to 82.7, with a normalized gain of 0.54, indicating moderate improvement. Mastery learning rose from 40.0% to 86.7%. Qualitative findings suggest that Quizizz Paper Mode supported inclusive participation, while team-based competition fostered motivation, collaboration, and classroom engagement. The findings remain limited by the absence of a control group